Salience and Timely Compliance: Evidence from Speeding Tickets - Libor Dušek; Nicolas Pardo; Christian Traxler (Journal of Policy Analysis and Management, 2022)
This paper studies the enforcement of fines, and, in particular, the effects of simplification and salience nudges on timely payments. In a randomized controlled trial, we add cover letters to 80,000 payment notifications for speeding. The letters increase the salience of the payment deadline, the late penalty, or both. Emphasizing only the deadline is not effective. Stressing the late penalty significantly and persistently increases payment rates. The effect is largest if both parameters are made salient. The most effective treatment yields a net revenue gain that covers approximately 25 percent of the labor costs of the ticket administration personnel. A survey experiment documents how the salience nudges alter prior (mis)perceptions about the communicated parameters. The survey results rationalize the differential effects of the treatments and, together with the evidence from the RCT, offer a broader framework for explaining why certain nudges are effective in some contexts but fail in others.
Keywords: 650